1971
DOI: 10.1037/h0031509
|View full text |Cite
|
Sign up to set email alerts
|

Flexibility and satisfaction with college major.

Abstract: The relationship between flexibility (as measured by the flexibility scale of the California Psychological Inventory) and satisfaction with college major was examined for 73 social science and 4S natural science students. It was predicted that those social science students who were most satisfied with their college major would be more flexible than those who were least satisfied, but those natural science students who were most satisfied with their major would be less flexible than their relatively dissatisfie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
(11 reference statements)
0
3
0
Order By: Relevance
“…Much of this early research reported specific traits that differed between students from some different academic majors. Some studies reported differences between science majors and humanities and social science majors (Banth & Mohan, 1985; Sherrick, Davenport, & Colina, 1971). Other studies reported differences between engineering majors (Nixon & Parsons, 1989) or business majors (Kipnis, Lane, & Berger, 1967; Lounsbury, Smith, Levy, Leong, & Gibson, 2009; Pringle, Dubois, & Yankee, 2010) and students from other majors.…”
Section: Personality Academic Major and Academic Outcomesmentioning
confidence: 99%
“…Much of this early research reported specific traits that differed between students from some different academic majors. Some studies reported differences between science majors and humanities and social science majors (Banth & Mohan, 1985; Sherrick, Davenport, & Colina, 1971). Other studies reported differences between engineering majors (Nixon & Parsons, 1989) or business majors (Kipnis, Lane, & Berger, 1967; Lounsbury, Smith, Levy, Leong, & Gibson, 2009; Pringle, Dubois, & Yankee, 2010) and students from other majors.…”
Section: Personality Academic Major and Academic Outcomesmentioning
confidence: 99%
“…Global (as opposed to facet) major satisfaction has infrequently been assessed. When major satisfaction is assessed globally, it is typically measured with a single item (e.g., Chartrand et al, 1992;Leong et al, 2005;Sherrick, Davenport, & Colina, 1970;Wachowiak, 1972;Ware & Pogge, 1980) that may lack reliability or with a measure that has unknown psychometric properties (e.g., Morrow, 1971;Nelson, 1982). Consequently, the need for a multi-item satisfaction measure with sound psychometric properties has been identified Lounsbury, Park, Sundstrom, Williamson, & Pemberton, 2004).…”
mentioning
confidence: 99%
“…Career adaptability (a measure of flexibility) has been correlated with major satisfaction (r = .35;. An analysis of variance comparing social science majors and natural science majors in terms of flexibility and major satisfaction found that social science majors who were more, as opposed to less, flexible were also more satisfied, but that natural science majors who were less, as opposed to more, flexible were more satisfied (F = 4.56, df = 2,112, p < .05; Sherrick, Davenport, & Colina, 1971). In a multiple regression, the personality trait emotionality was found to predict major satisfaction (β = -.12; Pozzebon, Ashton, & Visser, 2014).…”
Section: Academic Major Satisfactionmentioning
confidence: 98%